The influence of demographic changes on the development potential of communes of the West-Pomeranian province - Karmowska, Grażyna; Sobczyk, Andrzej (Wpływ zmian demograficznych na potencjał rozwojowy gmin województwa zachodniopomorskiego, 2019)
Development potential depends primarily on the area’s demographic situation, its capacity to attract new residents and the local community’s reproductive capacity. From the perspective of social and economic development, the demographic potential of local communities is an important element of the region’s development opportunities. This paper makes an attempt to evaluate the demographic situation of the communes of the West-Pomeranian province and their potential for development. To achieve that goal, a synthetic variable was used and Webb’s method was employed to create a typology of communes of similar demographic potential. The research conducted confirmed the variance in development potential between communes. Municipalities with a better demographic potential use ‘positional pension’ at the larger urban centers. The result is a ‘suction’ of the population, which affects the growth of budget revenues from real estate tax and the share of income tax from individuals
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 8, s. 7-21
Keywords: local development; development potential of communes; Webb's classification; synthetic variable; rozwój lokalny; potencjał rozwojowy gminy; klasyfikacja Webba; zmienna syntetyczna